Design and Characterisation of Bi-layer Tablets Containing Simvastatin as Sustained Release and Labetalol HCl as Immediate Release - Tambe, Sujit T.; Padekar, Harshad B.; Dhobale, S.M.; Jadhav, S.L. (Journal of Drug Delivery and Therapeutics, 2019)
The objective of present investigation is to design and characterise sustained release Simvastatin and immediate release of Labetalol HCl, a bi-layer tablet. The combination therapy of Simvastatin and Labetalol HCl can be useful in severe cardiovascular disease such as hypertension, angina pectoris, congestive heart failure which may occur along with increasing cholesterol level in the blood, while this combination remain preferable choice to the patient as compared to single dosage form. The bi-layer tablet is suitable for sequential release of two drugs in combination which are compatible with each other. Objective of present investigation is to prepare bi-layer tablet in which one layer is sustained while another one is immediate release. For the preparation of bi-layer tablet, different super disintegrants like cross carmellose cellulose, micro crystalline cellulose is used for immediate release and HPMC and Carbapol as controlled release polymer. The pre-formulation parameter such as solubility, melting point, compatibility study (FTIR) were studied. Pre-compression parameter such as angle of repose, bulk density, tapped density, hausner’s ratio and compressibility index were studied. The tablets were evaluated by physical and chemical parameters such as weight uniformity, hardness, thickness, diameter, friability, drug content, disintegration time and in-vitro drug release. The dissolution data were subjected to various release kinetic model to recognize the mechanism of drug release.Keyword: sustained release tablet, bi-layer tablet, Simvastatin, Labetalol HCl.